2004
DOI: 10.1071/bt03159
|View full text |Cite
|
Sign up to set email alerts
|

Pollination ecology of the Australian cycad Lepidozamia peroffskyana (Zamiaceae)

Abstract: Abstract. Experiments carried out to investigate the reproductive ecology of the Australian cycad Lepidozamia peroffskyana (Regal, Bull. Soc. Imp. Nat. Mosc. 1857, 1: 184) revealed that this species is pollinated exclusively by host-specific Tranes weevils (Pascoe 1875). The weevils carry out their life cycle within the tissues of the male cones but also visit the female cones in large numbers. Female cones from which insects (but not wind) were excluded had a pollination rate that was essentially zero. In co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
51
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(55 citation statements)
references
References 35 publications
4
51
0
Order By: Relevance
“…[6][7][8]. Similar experiments and observations on other continents indicate the same for other genera of cycads [9][10][11][12][13][14][15][16][17][18][19]. In a recent seminal work on guidelines for cycad classification, insect symbionts of cycads were identified as having a potentially important impact on cycad classification: "Insects appear to be the primary vectors for pollination [ .…”
Section: Introductionsupporting
confidence: 48%
“…[6][7][8]. Similar experiments and observations on other continents indicate the same for other genera of cycads [9][10][11][12][13][14][15][16][17][18][19]. In a recent seminal work on guidelines for cycad classification, insect symbionts of cycads were identified as having a potentially important impact on cycad classification: "Insects appear to be the primary vectors for pollination [ .…”
Section: Introductionsupporting
confidence: 48%
“…Insects are involved in the pollination of the most plesiomorphic, extant cycad taxon, Cycas L. of the Cycadaceae (Ornduff, 1991;Yang et al, 1999;Kono & Tobe, 2007). Extant Zamiaceae and Stangeriaceae, whose earliest occurrences are Jurassic, are obligately insect pollinated by a spectrum of beetle pollinators, such as Boganiidae, Erotylidae, Belidae, and Curculionidae (Norstog, 1987;Norstog & Fawcett, 1989;Crowson, 1991;Donaldson, 1992;Forster et al, 1994;Norstog et al, 1995;Tang, 1997;Wilson, 2002;Hall et al, 2004;Oberprieler, 2004), and also by the aeolothripid thrips Cycadothrips (Okajima, 2000;Mound & Terry, 2001;Terry et al, 2005). It has been suggested that most of these associations are ancient and mid Mesozoic in origin.…”
Section: Plant Features Associated With Mandibulate Insect Pollinatorsmentioning
confidence: 99%
“…The pollination system of cycads typically involves broodsite mutualisms in which the pollinators are insect herbivores whose larvae feed on male cone tissues and female cones are pollinated when visited by mistake [25][26][27][28][29]. Pollination in these dioecious gymnosperms is mediated by specific cone volatile compounds [30].…”
Section: Introductionmentioning
confidence: 99%